Do We Glorify Violence in Our Culture? Psychoanalytic Perspectives on Media and Violence. Issue 6 (17th August 2016) - Nayar-Akhtar, Monisha C.
ABSTRACT: The relationship between media and violence is a complex and perplexing one. A sample of the numerous statistics and studies on this subject illustrates growing developmental implications (as in children who view media violence are more likely to be aggressive), socio-cultural influences (increasing portrayals of real-life violence), as well as political involvement (leaders of a nation asking for the Entertainment Industry to not glorify gun violence). Finally, increasing difficulties in discerning fantasy and real life suggests that at an intrapsychic level, a core function of imaginative play (Winnicott, 1971), an essential ingredient of childhood development, may also be further compromised. Yet, although the escalation of violence in and by the media is ubiquitous and undeniable, it is also true that not all individuals exposed to such violence act upon it, nor do they experience all the developmental challenges as illuminated by research data. Furthermore, significant variations in both cultural and individual expression of violence suggests that other factors more pertinent to intrapsychic functioning, as well as group processes, may also be at play. Last, cyberspace technology has substantially altered the playing field for the depiction of violence with some interesting results. These concerns will be explored in this article.